(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2016)
Present work reports the synthesis of pure TiO2 and (Sn-Ti)O2 nanocomposite, its characterization and performance as Liquefied Petroleum Gas (LPG) Sensor. Thick films of both the materials were prepared by using screen printing technique. After that these were investigated through SEM. SEM image of pure TiO2 shows that grains are random in shape having pores. The grains observed on the (Sn-Ti)O2 thick-film surface are spherical in shape and more porous than pure TiO2. Further at room temperature, the films were exposed to LPG in a controlled gas chamber and variations in resistance with the concentrations of LPG were observed. The maximum value of average sensitivity for pure TiO2 and (Sn-Ti)O2 thick-film were found 3.0 and 11 respectively for 2 vol.% of LPG. Sensor responses as a function of exposure and response times were also estimated and maximum sensor response for pure TiO2 and (Sn-Ti)O2 thick-film were found 207 and 1040 respectively.